Scenario‐mining for level 4 automated vehicle safety assessment from real accident situations in urban areas using a natural language process - Park, Sangmin; Park, Sungho; Jeong, Harim; Yun, Ilsoo; So, Jaehyun (Sensors, 2021)
As the research and development activities of automated vehicles have been active in recent years, developing test scenarios and methods has become necessary to evaluate and ensure their safety. Based on the current context, this study developed an automated vehicle test scenario derivation methodology using traffic accident data and a natural language processing technique. The natural language processing technique‐based test scenario mining methodology generated 16 functional test scenarios for urban arterials and 38 scenarios for intersections in urban areas. The proposed methodology was validated by determining the number of traffic accident records that can be explained by the resulting test scenarios. That is, the resulting test scenarios are valid and represent a matching rate between the test scenarios and the increased number of traffic accident records. The resulting functional scenarios generated by the proposed methodology account for 43.69% and 27.63% of the actual traffic accidents for urban arterial and intersection scenarios, re-spectively.
Keywords: Accident data; Accident situation; Automated vehicles; Language processing techniques; Level 4; Natural language process; Research activities; Scenario‐mining; Test scenario; Urban areas; Accidents, Traffic; Language; Safety; Accident data; Automated vehicle; Natural language process; Safety; Scenario‐mining